Endothelial Dysfunction - A Novel Paradigm 2023
DOI: 10.5772/intechopen.108108
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Gene Variants of Endothelin-1: A Critical Regulator of Endothelial Dysfunction

Abstract: Endothelial dysfunction (ED) is an early marker of development of cardiovascular diseases and is closely related to clinical events in patients with atherosclerosis and hypertension. Endothelin-1 (ET-1), a potent vasoconstrictor, and nitic oxide (NO), a potent vasodilator, produced in endothelial cells are leading molecules which regulate vascular function. Failure of the physiological balance between these two molecules, often aggravated by increased production and biological activity of ET-1, commonly reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…It has been previously shown that NOS3 protects against systemic inflammation while reducing ICAM-1 and IL6 expression, which makes it an interesting potential therapeutic target for inflammation treatment [57]. During inflammation, the disruption of vascular homeostasis leads to upregulation of EDN1, which acts as an antagonist to NOS3 [58]. This behaviour of EDN1 has been confirmed by our investigation of EDN1 gene expression, showing a significant upregulation in endothelial cells under inflammatory conditions.…”
Section: Discussionsupporting
confidence: 83%
“…It has been previously shown that NOS3 protects against systemic inflammation while reducing ICAM-1 and IL6 expression, which makes it an interesting potential therapeutic target for inflammation treatment [57]. During inflammation, the disruption of vascular homeostasis leads to upregulation of EDN1, which acts as an antagonist to NOS3 [58]. This behaviour of EDN1 has been confirmed by our investigation of EDN1 gene expression, showing a significant upregulation in endothelial cells under inflammatory conditions.…”
Section: Discussionsupporting
confidence: 83%
“…[21][22][23] Endothelin-1 is a potent endogenous vasoconstrictor produced primarily by the vascular endothelium. [24][25][26] As a vasoconstrictor it contributes to increased tone in atherosclerotic coronary arteries and is involved in endothelial dysfunction, inflammation, and vascular remodeling. [27][28][29] A meta-analysis by Windecker et al reported a reduction in mortality and incidence of acute myocardial infarction (AMI) with revascularization vs. medical therapy alone, in CCS patients when revascularization was performed with a coronary artery bypass graft (CABG) or a new generation of drug-eluting stent (DES) instead of the earlier DES (bare metal stent) or balloon angioplasty alone.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Endothelin-1 is a potent endogenous vasoconstrictor produced primarily by the vascular endothelium. [24][25][26] As a vasoconstrictor it contributes to increased tone in atherosclerotic coronary arteries and is involved in endothelial dysfunction, inflammation, and vascular remodeling. [27][28][29] A meta-analysis by Windecker et al reported a reduction in mortality and incidence of acute myocardial infarction (AMI) with revascularization vs. medical therapy alone, in CCS patients when revascularization was performed with a coronary artery bypass graft (CABG) or a new generation of drug-eluting stent (DES) instead of the earlier bare metal stent (BMS) or balloon angioplasty alone.…”
Section: Introductionmentioning
confidence: 99%